2019
DOI: 10.1590/0034-761220180026
|View full text |Cite
|
Sign up to set email alerts
|

Impactos do Programa Bolsa Família no mercado de trabalho dos municípios brasileiros

Abstract: Resumo Beneficiando cerca de 14 milhões de famílias brasileiras, o Programa Bolsa Família (PBF) é um dos mais importantes programas brasileiros de transferência condicionada de renda dos últimos anos. A investigação dos impactos do PBF, no mercado de trabalho formal dos 5.570 municípios brasileiros, no período de 2004 a 2013, constitui o principal objetivo deste artigo. Usando dados totais de cada um dos municípios da União, obtidos no Cadastro Único do Ministério do Desenvolvimento Social (MDS) e no Cadastro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…On the educational front, a systematic review found that, regardless of the unit of analysis, whether student or school, the Brazilian Income Transfer Program was able to produce positive results, especially for school attendance and dropout rates in the pre-pandemic context 20 . Municipal economies benefited from the Brazilian Income Transfer Program, considering the association found between benefits paid by the program and the number of people with formal occupation and between benefits and total work income in Brazilian cities 21 . There are positive impacts on the empowerment of women, who today represent more than 80% of the beneficiaries, observed on different levels, namely on the individual, family, and community levels 22 .…”
mentioning
confidence: 99%
“…On the educational front, a systematic review found that, regardless of the unit of analysis, whether student or school, the Brazilian Income Transfer Program was able to produce positive results, especially for school attendance and dropout rates in the pre-pandemic context 20 . Municipal economies benefited from the Brazilian Income Transfer Program, considering the association found between benefits paid by the program and the number of people with formal occupation and between benefits and total work income in Brazilian cities 21 . There are positive impacts on the empowerment of women, who today represent more than 80% of the beneficiaries, observed on different levels, namely on the individual, family, and community levels 22 .…”
mentioning
confidence: 99%
“…Na frente educacional, uma revisão sistemática apurou que, independentemente da unidade de análise (se era aluno ou escola), o Programa Bolsa Família mostrou-se capaz de produzir resultados positivos, principalmente em relação à frequência escolar e às taxas de abandono, no contexto pré-pandemia 20 . As economias municipais beneficiaram-se do Programa Bolsa Família, diante da associação constatada entre benefícios pagos pelo programa e quantidade de pessoas com ocupação formal e entre benefícios e total de rendimentos do trabalho nas cidades brasileiras 21 . Há impactos positivos no empoderamento das mulheres, que hoje representam mais de 80% das titulares do benefício, constatados em diferentes frentes, a exemplo da individual, da familiar e da comunitária 22 11 , desconstrução institucional 14 e descoordenação federativa 23 nesta área durante os governos Temer e Bolsonaro.…”
unclassified
“…En el frente educativo, una revisión sistemática constató que, independientemente de la unidad de análisis, ya sea el estudiante o la escuela, el Programa Bolsa Familia demostró ser capaz de producir resultados positivos, principalmente para la asistencia escolar y las tasas de deserción, en el contexto prepandemia 20 . Las economías municipales se beneficiaron del Programa Bolsa Familia, ante la asociación constatada entre los beneficios pagados por el programa y la cantidad de personas con empleo formal y entre los beneficios y los ingresos totales del trabajo en las ciudades brasileñas 21 . Existen impactos positivos en el empoderamiento de las mujeres, quienes hoy representan más del 80% de las titulares del beneficio, constatados en diferentes frentes, como el individual, el familiar y el comunitario 22 .…”
unclassified